Turkish League Against Rheumatism National Recommendations for the Management of Ankylosing Spondylitis - Bodur, Hatice; Sivas, Filiz; Yilmaz, Ozlem; Ozgocmen, Salih; Gunaydin, Rezzan; Kaya, Taciser; Yanik, Burcu Corekci (Turkish League Against Rheumatism, 2011)
Objectives: To develop Turkish League Against Rheumatism (TLAR) National Recommendations for the management of ankylosing spondylitis (AS). Materials and methods: A scientific committee of 25 experts consisting of six rheumatologists and 19 physical medicine and rehabilitation specialists was formed by TLAR. Recommendations were based on the 2006 ASsessment in Ankylosing Spondylitis International Working Group(ASAS)/European League Against Rheumatism (EULAR) recommendations and a systematic review of associated publications between January 2005 and September 2010. A Delphi process was used to develop the recommendations. Twelve major recommendations were constructed for the management of AS. Voting using a numerical rating scale assessed the strength of each recommendation. Results: The 12 recommendations include patient assessment, patient follow-up along with pharmacological and non-pharmacological methods. Some minor additions and changes have been made to the ASAS/EULAR recommendations. All of the recommendations had sufficient strength. Conclusion: National recommendations for the management of AS were developed based on scientific evidence and consensus expert opinion. These recommendations will be updated regularly in accordance with recent developments.
Türkiye romatizma araştırma ve savaş derne?i ankilozan spondilit ulusal tedavi önerileri
Keywords: Ankylosing spondylitis; national recommendations; treatment